2003
DOI: 10.1007/bf02706215
|View full text |Cite
|
Sign up to set email alerts
|

Molecular screening for Yq microdeletion in men with idiopathic oligozoospermia and azoospermia

Abstract: Infertility affects 15% couples attempting pregnancy and in 40-50% of these cases the male partner has qualitative or quantitative abnormalities of sperm production. Microdeletions in the azoospermia factor (AZF) region on the long arm of the Y chromosome are known to be associated with spermatogenic failure and have been used to define three regions on Yq (AZFa, AZFb and AZFc) which are critical for spermatogenesis and are recurrently deleted in infertile males. Semen analysis was carried out on one hundred a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 13 publications
1
30
1
3
Order By: Relevance
“…The reason is probably the strict selection criteria applied in our study as well as geographic and ethnic differences. Within India, studies have been carried out in different regions, which showed a frequency between 5% and 9.5% (21)(22)(23). The selection criteria in these were also different from the criteria used in our study, the number of STSs used were variable.…”
Section: Discussionmentioning
confidence: 69%
“…The reason is probably the strict selection criteria applied in our study as well as geographic and ethnic differences. Within India, studies have been carried out in different regions, which showed a frequency between 5% and 9.5% (21)(22)(23). The selection criteria in these were also different from the criteria used in our study, the number of STSs used were variable.…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, about 10% to 15% of idiopathic cases of azoospermia and severe oligozoospermia have microdeletions in AZF regions as the etiologic factor [12][13][14]. The frequency of Y chromosome microdeletions varies between 1% [15] and 55% [16] in the worldwide whereas the few studies performed in Asian male populations showed frequencies of 7.6% to 16.5% in Japan [17][18][19][20][21][22], 11.0% to 19.4% in China [23,24], 10.6% to 11.7% in Taiwan [25,26], 6.4% in Hong Kong [27] and 2.0% to 12.0% in India [12,28,29]. A recently published study reported that the cumulative frequency of Y chromosome microdeletions was 3.5 % in infertile males [30].…”
Section: Abstract Y Chromosome Microdeletion Chromosomal Abnormalitmentioning
confidence: 99%
“…A series of 9 specific STSs, mapped in the AZF region, and human zinc-finger protein-encoding genes (ZFX/ZFY) located on the X and Y chromosomes were selected. The ZFX/ZFY, acting as an internal control primers, were selected for molecular genetic analysis of microdeletion [13,14]. These specific STSs included SY84 and SY86 for AZFa, SY27, SY134, and SY143 for AZFb, SY157, SY254, and SY255 for AZFc, and SY152 for AZFd.…”
Section: Selection Of Primersmentioning
confidence: 99%